Geographical variation and population structure in the White-rumped Sandpiper Calidris fuscicollis as shown by morphology, mitochondrial DNA and carbon isotope ratios - L Wennerberg; Marcel Klaassen; Å Lindström (2002)
We studied the population structure of a high arctic breeding wader bird species, the White-rumped Sandpiper Calidris fuscicollis. Breeding adults, chicks and juveniles were sampled at seven localities throughout the species' breeding range in arctic Canada in 1999. The mitochondrial control region was analysed by DNA sequencing, feathers were analysed for carbon isotope ratios (C13/C12) by isotope ratio mass spectrometry, and morphological measurements were analysed using principal component analyses, taking the effect of sex into account (identified by molecular genetic methods). In general, our results support the notion that the White-rumped Sandpiper is a monotypic species with no subspecies, and most of the morphological and genetic variation occurs within sites. Nevertheless, some differences between sites were found. Birds from the two northernmost sites (Ellesmere and Devon Islands) had relatively longer bill and wing and shorter tarsus than birds sampled further south, possibly reflecting genetic differences between populations. The carbon isotope ratios were higher at the easternmost site (Baffin Island), revealing differences in the isotope content of the food. The mtDNA sequences showed no significant differentiation between sites and no pattern of isolation-by-distance was found. Based on the mtDNA variation, the species was estimated to have a long-term effective population size of approximately 9,000 females. The species shows no clear evidence of any population expansion or decline. Our results indicate that carbon isotope ratios, and possibly also certain mtDNA haplotypes, may be useful as tools for identifying the breeding origin of White-rumped Sandpipers on migration and wintering sites.